Nanotechnologies in Pancreatic Cancer Therapy - Ayesha Manzur; Adeolu Oluwasanmi; Darren Moss; Anthony Curtis; Clare Hoskins (MDPI AG, 2017)
Pancreatic cancer has been classified as a cancer of unmet need. After diagnosis the patient prognosis is dismal with few surviving over 5 years. Treatment regimes are highly patient variable and often the patients are too sick to undergo surgical resection or chemotherapy. These chemotherapies are not effective often because patients are diagnosed at late stages and tumour metastasis has occurred. Nanotechnology can be used in order to formulate potent anticancer agents to improve their physicochemical properties such as poor aqueous solubility or prolong circulation times after administration resulting in improved efficacy. Studies have reported the use of nanotechnologies to improve the efficacy of gemcitabine (the current first line treatment) as well as investigating the potential of using other drug molecules which have previously shown promise but were unable to be utilised due to the inability to administer through appropriate routes-often related to solubility. Of the nanotechnologies reported, many can offer site specific targeting to the site of action as well as a plethora of other multifunctional properties such as image guidance and controlled release. This review focuses on the use of the major nanotechnologies both under pre-clinical development and those which have recently been approved for use in pancreatic cancer therapy.